"Playing with Surgical Instruments (PlaSurIn)" game to train operating room novices how to set up basic surgical instruments: A validation study. (October 2021) - Nasiri, Morteza; Eslami, Jamshid; Rashidi, Neda; Paim, Crislaine Pires Padilha; Akbari, Fakhridokht; Torabizadeh, Camellia; Havaeji, Fahimeh Sadat; Goldmeier, Silvia; Abbasi, Mohammad
Abstract: Background: Game-based training has been considered as an alternative modality to traditional training in different perioperative nursing fields. Objectives: To describe the adaptation and validation process of " Playing with Tweezers ", a Portuguese game developed for novices to set up basic surgical instruments on the Mayo stand or a back table. Design: A validation study with three phases of translation, reconciliation, and evaluation (face, content, and construct validity). Settings: Several medical universities in Iran. Participants: Twelve students in a pilot translation test, 18 experts in the reconciliation phase, 20 experts in the face and content validity stages, and 120 students (72 novices, 26 intermediates, and 22 experts) in the construct validity stage. Methods: Following "forward-backward" translation from Portuguese to English, the English version of the game was appraised in the reconciliation phase using a 57-item questionnaire. To test face and content validity of the final version of the game, a 30-item questionnaire addressing different aspects of the game was completed. The students' game performance (remained time for game completion, obtained score, and error) was compared to assess the construct validity. Results: Minor differences were detected and resolved during the translation process. The English version of the game was reconciled in two sequential steps, and the final game called " Playing with Surgical Instruments ( PlaSurIn )" was developed. All the items regarding the face validity received 80–100% of positive responses. Moreover, regarding the content validity, all of the evaluated items obtained a content validity index of 0.90–1.0. Compared to the novices, the experts and intermediates received higher scores ( p < 0.001 in two cases) and fewer errors ( p < 0.001, p = 0.007). The remained time for game completion was significantly longer for experts than the novices ( p = 0.011). Conclusions: The " PlaSurIn ", as a virtual training strategy, can prepare novices to set up basic surgical instruments.